6 - Effet des caractéristiques pré-admissions et de l’expérience du système universitaire sur la persévérance aux études en enseignement supérieur : perspective de recherche en Afrique - Kobiané, Jean-François; Frenette, Eric; Loye, Alexis Salvador (Journal of Higher Education in Africa, 2022)
L’enseignement supérieur est considéré comme un moyen privilégié pour former une main-d’œuvre hautement qualifiée visant à assurer le progrès économique et social d’un pays. Romainville et Michaut 2012...mais les universités publiques africaines peinent généralement à maintenir les étudiants qui y accèdent . Zagré 2007The purpose of this article is to analyze the effect of pre-admission characteristics (family background, personal characteristics, previous school experience) and experience of the university system (class experiences, university resources including bursaries, loans or grants) on perseverance in higher education through a systematic review of the scientific literature, according to the nine stages proposed by Gough (2007). Despite operationalization based on various studies, pre-admission characteristics, experience of the university system and student perseverance are interrelated. One study proposes the mediating role of university system experience in the relationship between pre-admission characteristics and perseverance in higher education studies. This role is enhanced by the fact that it reduces pre-admission inequalities. The use of multi-year data is appropriate in estimating the longitudinal impact of the mediating role with a robust model such as Tinto’s (1997).